The Enhancing Teacher Quality Through Educational Qualifications in Indonesia: A Study of Legal Politics - Maryanto Maryanto; Bambang Sumardjoko; Muh Isna Nurdin Wibisana; Sharifah Osman (Unissula, 2025)
The quality of teachers is an essential factor in determining the efficacy of the national education system. In Indonesia, measures to improve teacher quality have increasingly concentrated on elevating educational qualification standards, influenced by regulatory frameworks and political goals. This study aims to examine the Legal Policies Regulating Teacher Education Qualifications and examine Directions for Achievement of Policies on Teacher Education Qualifications. This research examines major legislation, including the Teacher and Lecturer Law, and approriate government policies to explain the achievements and weaknesses of these campaigns. The research examines the political dynamics influencing educational reform, encompassing stakeholder interests, obstacles to policy execution, and the impact of decentralization. Research indicates that although more rigorous qualifying criteria can enhance teacher proficiency, effective policy implementation and continuous professional development are crucial for enduring advancement. The novelty of this research lies in the integrative effort to align the national educational legislative framework with educational best practices as the foundation for improving the quality of teaching across Indonesia.